Pesantren dan Pendidikan Perdamaian - Ulfa Masamah (Jurnal Pendidikan Islam, 2013)
Surakarta was a city that had a high intensity of religious social conflict that has to be managed as well as possible, transformed, and developed peace. This research is about the roles of Pesantren of Al Muayyad Windan in which its capacity to transform the conflict in Surakarta. The research findings showed that religious conflict transformation that could be done and based on the principle of the admission existence and the empowerment existence. The principles were based on the theology that was perceived and become as the motivation to do social changes and developed the transformative Islam unto the multiculturalism.